Exposure characterization and estimation of benchmark dose for cancer biomarkers in an occupational cohort of diesel engine testers. (November 2018) - Niu, Yong; Zhang, Xiao; Meng, Tao; Wang, Haisheng; Bin, Ping; Shen, Meili; Chen, Wen; Yu, Shanfa; Leng, Shuguang; Zheng, Yuxin
Abstract Exposure to diesel engine exhaust (DEE) was associated with various adverse health effects including lung cancer. Particle size distribution and profiles of organic compounds in both particle and gas phases of DEE that could provide valuable insights into related health effects were measured in a diesel engine testing workshop. Concentrations of urinary 6 mono-hydroxylated polycyclic aromatic hydrocarbons (OH-PAHs) in 137 DEE-exposed workers and 127 non-DEE-exposed workers were determined. Benchmark dose method was applied to estimate lower limit of benchmark dose (BMDL) of urinary OH-PAHs most specific to DEE exposure for previously reported cancer biomarkers. We found that 84.3% of diesel exhaust particles were ultrafine particles. Indeno[123-cd]pyrene and phenanthrene were the most abundant carcinogenic and noncarcinogenic PAHs in the particle phase of DEE, respectively. Principal component analysis demonstrated that urinary hydroxyphenanthrene (OHPhe) had highest loading value on principal component (PC) representative of DEE exposure and lowest loading value on PC representative of smoking status. BMDLs of urinary OHPhe from best-fitting models for cancer biomarkers including micronucleus and 1, N6 -ethenodeoxyadenosine were 1.08 μg/g creatinine and 2.82 μg/g creatinine, respectively. These results provided basis for understanding DEE exposure induced health effects and potential threshold for regulating DEE levels in an occupational setting.